The effect of a purpose-built memory support unit on the transition to high level dementia care; Perspectives of multiple participants. Issue 3 (June 2020) - Broadbent, Marc; Gilbert, Sandra
Abstract: Background: Australia faces the challenge of an ageing population. The incidence of people with dementia unable to live in the community is expected to rise leading to demands on care facilities to provide specialised care. This paper reports on the effect a purpose-built Memory Support Unit has on multiple participants during the transition from home, or an aged care residence, to high level dementia care. Aim: The aim of this research was to understand the effect of a purpose-built Memory Support Unit on the experiences of those with dementia who are transitioning into this environment, their family or carers and staff. Method: A qualitative descriptive methodology was adopted to frame the research. Face-to-face interviews were conducted with nine family members, two residents and three Registered Nurses. Findings: A purpose-built Memory Support Unit may have a positive effect on the older person, their families, carers and staff, thus improving the experience of all participants as the older person transitions into dementia care. Optimising design of the physical environment may foster a more person-centered orientation to care and positive outcomes for residents, family members or carers and staff. Conclusions: Purpose built environments may have a meaningful subjective effect on the wellbeing of older people during the transition from their residence to permanent dementia care, their family, carers and staff. It is recommended that architects, funding agencies and aged care providers engage with the growing body of evidence that purpose-built environments, such as the Memory Support Unit, to enhance the quality of the experience of those transitioning to high level dementia care, their family or carers and staff.